Modeling the impact of agricultural managed aquifer recharge (Ag-MAR) on soil water and nitrogen dynamics of the growing season - Wenyi Cui; Tiantian Zhou; Elad Levintal; Cristina Prieto García; Isaya Kisekka; Helen E. Dahlke (Agricultural Water Management)
Agricultural managed aquifer recharge (Ag-MAR) is a practice aimed at sustaining groundwater reserves by utilizing farmland to recharge excess surface water into aquifers. Because fields are fertilized for crop production there are questions about how Ag-MAR may affect the leaching of legacy nitrate from fertilizer applications to groundwater or nitrogen transformations such as mineralization or denitrification. In this study, DSSAT was used to model the impact of different Ag-MAR practices (e.g. continuous or intermittent flooding for 8–20 days) prior to the growing season to estimate their effect on the growing season water and nitrogen budgets. The study uses soil physico-chemical, hydrologic, and processing tomato yield data from an Ag-MAR experiment in the Central Valley, California. Results show that the timing (e.g. Jan–Apr) and intermittency of flooding (e.g. continuous vs. wet-dry cycles) directly impact the amount of nitrate leached, and the residual amount of nitrate available at the beginning (May) of the growing season. Scheduling Ag-MAR closer to the growing season benefits the root zone water content and crop yield and can reduce growing season irrigation demand by 10 %, although these effects are less pronounced in sandy soils. Together these results show that continuous flooding for longer (e.g. 8–20 days) periods of time, well in advance of the growing season (> 2 months), provides the greatest recharge potential with no adverse effects on the growing season nitrogen budget. Early and continuous Ag-MAR promotes the mineralization of new nitrate which offsets nitrate leaching and allows for water and nitrogen fertilizer savings during the growing season.